The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1108/ijmpb-03-2021-0077
|View full text |Cite
|
Sign up to set email alerts
|

How do adoption choices influence public private partnership outcomes? Lessons from Spain and Portugal transport infrastructure

Abstract: Purpose Maximising real efficiency benefit (REB) is currently being replaced with access to private finance as core public–private partnership (PPP) adoption motive. This later choice focusses on short-term performance, compromising REB and the procurement of infrastructure that meets the need of the present and future generations, which the former accomplishes. The paper aims to review these observed changes to understand the rationales and significance behind such switch.Design/methodology/approach Secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…More importantly, the reference framework (refer to Figure 5) provides three main functions, along with 20 subfunctions, which can be used systematically by firms considering the multiple-level groups. Moreover, if the results are compared with other studies and the difference is described, some of the parts in Figure 5 remain true to previous studies concluded: (1) closeout claims [26]; (2) improvement of organisational ambidexterity [31][32][33]72,73]; (3) dispute settlement [23,77,79,81]; (4) claim phases and timeline [9,61,62]; (5) CMO maturity level [21]; (6) claim performance indicators [22,58]. However, as previous scholars have reported on OPM-related decisions [17,19,20], past research has not figured out how all of these behavioural-based concepts can be integrated into the design structure of CMO in firms' organisations.…”
Section: Discussion and Contributionsmentioning
confidence: 56%
See 3 more Smart Citations
“…More importantly, the reference framework (refer to Figure 5) provides three main functions, along with 20 subfunctions, which can be used systematically by firms considering the multiple-level groups. Moreover, if the results are compared with other studies and the difference is described, some of the parts in Figure 5 remain true to previous studies concluded: (1) closeout claims [26]; (2) improvement of organisational ambidexterity [31][32][33]72,73]; (3) dispute settlement [23,77,79,81]; (4) claim phases and timeline [9,61,62]; (5) CMO maturity level [21]; (6) claim performance indicators [22,58]. However, as previous scholars have reported on OPM-related decisions [17,19,20], past research has not figured out how all of these behavioural-based concepts can be integrated into the design structure of CMO in firms' organisations.…”
Section: Discussion and Contributionsmentioning
confidence: 56%
“…This study's principal contribution is that integrated X-inefficiency and ambidexterity theories [32,[63][64][65] (which capture the intra-firm irrational managerial decisions, particularly in international firms) can improve claim performance [22]. Specifically, this research contributes to current CMO literature by developing the reference framework on how different influences among the reference framework's elements lead to better organisational claim performance.…”
Section: Contributions To Theorymentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, the scholars Khan et al (2021) found that excellent PG boosts project performance, allowing for prompt and efficient risk management and control. In addition, Anago (2022) discovered that well-articulated and receptive governance configurations are significant PS elements for “public-private partnership” (PPP) initiatives. Although empirical research on the association between PS and PG is limited (Biesenthal and Wilden, 2014; PMI, 2016), it depicts a favorable trend.…”
Section: Relationship Of Project Governance With Project Successmentioning
confidence: 99%